A study of thermal performance of medium cost terraced houses at Shah Alam, Selangor / Md Hanafiah Amin Abdullah - Abdullah, Md Hanafiah Amin (2002)
Thermal comfort can be defined as a subjective assessment to the conditions of environment. Therefore this dissertation will focus on thermal comfort performance in the residential houses as case studies, which related to building orientation and their design and microclimate or local environment. The study also consider weather the occupants of these houses are satisfied with thermal condition of the houses that they lived in by measured the actual parameters of the thermal conditions. The study is important because the environment in many building, whatever domestic, commercial or industrial, is not at alt satisfactory, is because the various problems that arise are not well understood. Many of the problems that may occur from the demand and followed by limitation of land, architect designs residential houses without taking into consideration sun movement, wind direction and other climatic elements that influence thermal comfort. Tall building, which obstructs the wind flowing into the house, blocks the residential houses.